Understanding the rationales behind childbearing: A qualitative study based on extended theory of planned behavior - Babak Moeini; Amir Erfani; Majid Barati; Amin Doosti-Irani; Hatam Hosseini; Mokhtar Soheylizad (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Childbearing is the most important determinant of population fluctuations and its studies are more important than other population phenomena. Many factors are associated with childbearing, but individual factors associated with it have been less studied in a specific framework. The present study aimed to explore and identify the factors related to childbearing based on extended theory of planned behavior (ETPB). MATERIALS AND METHODS: This qualitative study was conducted among married women <35 years of age and married men whose spouses were under 35 years of age and lived in the City of Hamadan, Iran, in 2019. The data were collected by semistructured and face-to-face in-depth interviews and continued until the data saturation was reached. Overall, 15 interviews were conducted with 17 people. The data were analyzed, using a directed content analysis approach. RESULTS: The data analysis resulted in the extraction of 28 main codes, 9 subcategories, and 4 themes, which were correspond to constructs of the theory, consisting of attitudes, subjective norms, perceived behavioral control, and social support in the field of childbearing. The main predictors were attitude toward childbearing and perceived control. CONCLUSION: The findings of this study showed that ETPB has a potential to explain the intention and behavior of childbearing. The ETPB makes it possible to understand many of the factors associated with childbearing. The results of this study could be the basis for designing appropriate data collection instrument in quantitative studies and vast surveys.